1990
DOI: 10.1007/bf00034493
|View full text |Cite
|
Sign up to set email alerts
|

Effect of silver nitrate on long-term culture and regeneration of callus from Brassica oleracea var. gemmifera

Abstract: Incorporation of AgNO 3 (1-10mg 1 -l) into the culture medium of Brassica oleracea var. gemmifera callus significantly improved growth and allowed long-term callus culture. In the absence of AgNO3, callus died shortly after removal from the hypocotyl explants. Regeneration of shoots from callus on low-hormone medium was also enhanced by AgNO 3 . Significant differences in shoot production were found between the three genotypes examined. Cv. Aries produced large numbers of shoots even in the absence of AgNO3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 15 publications
(17 reference statements)
2
12
1
Order By: Relevance
“…This has also been observed by Ozcan et al (1992). The concentration of silver nitrate used in this study (1 uM) was lower than that reported to have a positive influence on regeneration in other Block, 1988;Chi & Pua, 1989;Chi et al, 1990;Williams et al, 1990), but raising the concentration to 10 uM totally inhibited rooting in our experiments (results not shown). Inhibition of root regeneration was at its most evident after one month on rooting medium, as the rooting frequency (67%) obtained for shoots from shoot culture medium without silver nitrate was reduced to 26% when silver nitrate was filter sterilized into the medium (Table 2 treatments 2 and 5).…”
Section: Resultscontrasting
confidence: 71%
“…This has also been observed by Ozcan et al (1992). The concentration of silver nitrate used in this study (1 uM) was lower than that reported to have a positive influence on regeneration in other Block, 1988;Chi & Pua, 1989;Chi et al, 1990;Williams et al, 1990), but raising the concentration to 10 uM totally inhibited rooting in our experiments (results not shown). Inhibition of root regeneration was at its most evident after one month on rooting medium, as the rooting frequency (67%) obtained for shoots from shoot culture medium without silver nitrate was reduced to 26% when silver nitrate was filter sterilized into the medium (Table 2 treatments 2 and 5).…”
Section: Resultscontrasting
confidence: 71%
“…However, even recalcitrant B. rapa and other species have been triggered to develop shoots by applying ethylene inhibitors like aminoethoxyvinylglycine and silver nitrate (Chi et al 1990, Williams et al 1990, Sethi et al 1990, Palmer 1992, Pua and Chi 1993. Some transformation protocols claim the inclusion of silver nitrate to be obligatory for suflicient shoot regeneration , Pental et al 1993, particularly when kanamycin is used as a selectable marker (Mukhopadhyay et al 1992).…”
Section: Tissue Culture and Plant Regenerationmentioning
confidence: 99%
“…On the other hand, the inhibitory effect of ethylene on shoot formation has been altered by inhibitors of either ethylene action or ethylene production. Thus, incorporation of AgNO 3 in the culture medium promoted shoot regeneration from callus of Brassica oleracea (Williams et al 1990). Also, in some other members of the Cruciferae family addition of the ethylene inhibitors AgNO 3 or amino-ethyoxyvinyl-glycine (AVG) in the culture medium enhanced shoot regeneration from seedling explants (Pua et al 1990).…”
Section: Introductionmentioning
confidence: 99%